2023
DOI: 10.1111/obr.13602
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular complications of obesity and diabetes—Role of bariatric surgery

Abstract: SummaryBariatric surgery in people with obesity can lead to long‐term remission of type 2 diabetes mellitus (T2DM) and a reduction in the incidence of macrovascular complications. The impact of bariatric surgery on microvascular complications is less clear. In this narrative review, we sought to evaluate the effect of bariatric surgery on microvascular complications in patients with and without diabetes. The risk of developing microvascular complications is increased in people with obesity, and this is amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 174 publications
0
4
0
Order By: Relevance
“…Bariatric surgery is well established as a highly effective intervention in chronic severe obesity, leading to the resolution of comorbidities associated with obesity such as T2D, hypertension, hyperlipidaemia, OSA, and microvascular disease, as well as a reduction in mortality in patients over the long term [ 8 , 17 , 18 ]. The prospective Swedish Obese Subjects study concluded that bariatric surgery was superior to conventional treatment in terms of reduction in mortality and beneficial effects on comorbidities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery is well established as a highly effective intervention in chronic severe obesity, leading to the resolution of comorbidities associated with obesity such as T2D, hypertension, hyperlipidaemia, OSA, and microvascular disease, as well as a reduction in mortality in patients over the long term [ 8 , 17 , 18 ]. The prospective Swedish Obese Subjects study concluded that bariatric surgery was superior to conventional treatment in terms of reduction in mortality and beneficial effects on comorbidities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery, the most effective and durable weight loss intervention, reduces rates of metabolic and obesityassociated diseases [9,10]. However, bariatric surgery has been associated with temporarily increased serum uric acid levels and gout attacks in the immediate postoperative period in a study of 60 patients with type 2 diabetes undergoing sleeve gastrectomy [11], and another study of 99 patients with pre-existing gout who underwent bariatric surgery compared to patients undergoing non-surgical weight management [12].…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular complications of type 2 diabetes mellitus(T2DM) refer to the complications arising from structural and functional changes in the microvasculature in T2DM. These include T2DM retinopathy, T2DM neuropathy, and T2DM nephropathy ( 1 , 2 ). As the specific pathogenesis of microvascular complications in T2DM is not yet clear, and the onset of these complications is often insidious, they are typically diagnosed at a more advanced stage in clinical settings.…”
Section: Introductionmentioning
confidence: 99%